Method of detecting interaction paramaters between the physical model valet and grunt (Международный научный журнал «Инженер», 2026)
This article presents the procedures and methods for conducting experimental work in determining thelaws of interaction of soils with a physical model working body in a laboratory setting. In particular,devices consisting of a physical model, a soil corridor and a movable trolley valets are given, which areused in conducting experimental work. An explanation has also been cited for the clay grunts used tocarry out experimental work. In particular, the values the moisture intervals of the soils , compactioncoefficients, indicators of the number of plasticity are shown in the table. An expression that determinesthe moisture content of the soil has been cited. Graphs are constructed showing the relationship ofparameters interconnected by the soils moisture feedback. In particular, when the values of thecompaction coefficients differ, the internal friction angle of the soils and the state of moisture dependenceof the tensile force magnitudes are expressed, as well as the description of the physical model used in theexperiment and the physical mechanical properties of the soils used are also given.